Ruang Lingkup Maqasid dalam Tafsir al-Tahrir wa’l-Tanwir - amir ahmad nabil; Tasnim Abdul Rahman (Institut Agama Islam Persis Bandung, 2026)
the paper examines underlying topic and scope of maqasid shariah advocated by muhammad al-tahir ibn ashur in his seminar work of tafsir al-tahrir wa al-tanwir